Darwin's dangerous idea : evolution and the meanings of life - Dennett, D. C. (Daniel Clement) (London : Penguin, 1996)
In this book the author demonstrates the power of the theory of natural selection and shows how Darwin's great idea transforms and illuminates our traditional view of our place in the universe.
Keywords: Natural selection; Evolution (Biology) -- Philosophy; Human evolution -- Philosophy; Darwin, Charles, -- 1809-1882.; Darwin, Charles, -- 1809-1882 -- Criticism and interpretation